PENGARUH LINGKUNGAN KELUARGA TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PAI (STUDI SURVEI SMKN 40 JAKARTA TIMUR) - Kamilatul Millah; Kunaenih; Syarifah Amirah; Firdaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of the family environment as the first and primary educational setting that plays a role in shaping character, study habits, and students' academic success. Parental attention, parenting styles, the learning atmosphere at home, and family support are suspected to influence students' learning outcomes, especially in Islamic Religious Education (PAI) subjects. However, there are still students whose PAI learning outcomes are not optimal, making research necessary to understand the influence of the family environment on students' learning outcomes. This study aims to analyze the impact of the family environment on students' learning outcomes in PAI subjects and to determine the extent of the family's contribution to these learning outcomes. The research uses a quantitative approach with a descriptive survey method. The research population consists of 215 tenth-grade students at SMKN 40 Jakarta, with a sample of A total of 69 students were selected using the Slovin formula with a 10% margin of error through purposive sampling. Data were collected through questionnaires, documentation, and literature studies, then analyzed using the Product Moment correlation test and the coefficient of determination. The results showed that there is a positive and significant effect of the family environment on students' learning outcomes in PAI subjects. The correlation coefficient value of 0.627 indicates a fairly strong relationship and is higher than the r table value, so the alternative hypothesis is accepted. The coefficient of determination (R Square) value of 0.394 shows that the family environment contributes 39.4% to students' learning outcomes, while the remaining 60.6% is influenced by other factors outside the study. Therefore, the better the family environment, the better the students' learning outcomes in PAI subjects.